Психологічний аналіз особливостей прояву професійних деформацій особистості на різних етапах її професіоналізації - Мудрик, Алла Богданівна; Mudryk Alla B. (Кам'янець-Подільський національний уніерситет імені Івана Огієнка, 2014)
У статті здійснений теоретичний аналіз понять «професійні деструкції», «професійні деформації», «синдром емоційного вигорання»; виділені та сформульовані основні концептуальні положення щодо розвитку професійних деформацій та деструкцій особистості; деталізовані основні психологічні детермінанти виникнення професійних деструкцій особистості. Емпірично досліджені особливості прояву професійних деформацій особистості на різних етапах її професіоналізації.

The article is concerned with one of the most essential practical problems of the present time – how to care about occupational health of specialist and the formation of a harmoniously developed personality. The theoretical analysis of the concepts of "professional destructions", "professional deformations", "burnout syndrome" was conducted. Differentiated and formulated the basic conceptual statements about the development of professional deformations and destructions of the individual, elaborated basic psychological determinants of the emergence of professional destruction of personality. Empirical studies of expression of professional destructions at different stages of professional development were conducted. Logic of design of program empirical research and diagnostic of professional deformations in practical psychologists with different experience of professional work was concerned with the study of emotional burnout syndrome symptoms and the emotional states such as anxiety, depression, social frustration, neurotization and the indicators of wellness, health, activity and mood.
Psyhological analysis of the personality’s professional deformations display at different stages of professional development
Keywords: професійні деструкції; професійні деформації; синдром емоційного вигорання; професійне становлення особистості; стадії професіоналізації особистості; professional destructions; professional deformations; burnout syndrome; professional development of personality; stages of personality professionalization development